Comparative Analysis of Anti-Capitalist Narratives in Hizb ut-Tahrir Movements in Indonesia and Malaysia - Aswar, Hasbi (Dialogia, 2024)
This study explores the narrative of anti-capitalism through the perspective of Islamic political movements by comparing the Hizb ut-Tahrir movement in Indonesia and Malaysia. Capitalism has been a global topic of conversation with diverse impacts on societies, both positive and negative. However, criticisms have emerged due to the various damages and social impacts experienced in different countries. This research investigates how Hizb ut-Tahrir in Indonesia and Malaysia responds to the impact of capitalism in their respective countries through the lens of Islamic ideology. The study employs a qualitative approach with comparative analysis techniques, utilizing data collected from documents and literature related to the Hizb ut-Tahrir movement in both countries. The results reveal that Hizb ut-Tahrir in Indonesia and Malaysia views capitalism as a system incompatible with Islamic principles. They critique the capitalist system for fostering injustice, inequality, and the oppression of marginalized populations. Additionally, Hizb ut-Tahrir in Indonesia and Malaysia propose alternative Islamic-based economic systems as solutions to global economic problems.